Aplicaciones tecnológicas del molino para pulverizar granos en procesos de transformación Agroindustrial. - Pilicita Pilicita, Christian Javier (2023)
Knowing the use and operation of the machinery in the university facilities is of vital importance to guarantee the safety of professors and students by providing clear and precise instructions for its correct operation, minimizing the risk of accidents and promoting the efficient use of the equipment. The manual for the use and operation of the grain pulverizer mill includes the necessary procedures to guarantee the quality and safety in its execution, the manual offers general guidelines to be followed during the whole process, starting with the inspection of the equipment, routine, preventive, corrective, The manual offers general guidelines to be followed during the whole process, starting with the inspection of the equipment, routine, preventive and corrective maintenance, the manual offers general guidelines to be followed during the whole process, starting with the inspection of the equipment, routine, preventive and corrective maintenance, routine, preventive and corrective maintenance, routine, preventive and corrective maintenance, until the final product is obtained and the machinery is properly cleaned according to the discs used and products obtained, through demonstrative practices such as the preparation of peanut paste, coffee beans, pulverized rice husks using stone discs and crushed corn using metal discs according to the calibration and fineness of the milling process; the purpose of the project is to improve the practical knowledge of the academic institution, increasing the development and innovation of research projects within the Agroindustry Career.